Biomechanical Evaluation of Double-Strand (Looped) and Single-Strand Polyamide Multifilament Suture: Influence of Knot and Suture Size. (September 2015) - Netscher, David T.; Badal, Justin J.; Yang, Jonathan; Kaufman, Yoav; Alexander, Jerry; Noble, Philip
Background: Flexor tendon repair in zone II remains a vexing problem. Repair techniques have been developed to strengthen and optimize the number of core strands crossing a repair. A polyamide looped suture doubles the number of core strands for every needle path. This simplifies repairs, but the knot remains a potential weakness. The purpose of our study was to create a biomechanical model used to evaluate the bulky knot of a looped suture as it may be weaker, resulting in greater deformation. Methods: Using machined steel rods to hold our suture constructs, we compared four different knot configurations using looped and non-looped sutures in 3-0 and 4-0 varieties using a four-core strand technique. The constructs were tested under increased cyclic loading recording both forces applied and suture construct lengthening ("clinical gapping") and ultimate breaking strength. Results: During continuous periods of cyclic loading, we measured permanent deformation and ultimate breaking strength. Permanent deformation results when there is no recoverable change after force removal defined as a permanent rod separation (or gapping) of 2 mm. Four-strand 3-0 and 4-0 looped sutures failed at 39.9 and 27.1 N faring worse than a four-strand non-looped suture which reached a rod separation of 2 mm at 60.7 and 41.3 N. The ultimate breaking strength demonstrated absolute failure (construct rupture) with the 3-0 looped suture breaking at the knot at 50.3 N and the non-looped suture at 61.5 N. For the 4-0 suture, these values were 32.4 and 41.76 N. Conclusion: Within the constraints of this model, a looped suture fared worse than a non-looped suture especially when comparing 4-0 and 3-0 sutures. However, two-knot 3-0 looped suture constructs did resist the force generally accepted as occurring with early non-resistive tendon motion protocols, while two-knot 4-0 looped suture constructs did not. Clinical Relevance: This paper provides a description of a model to evaluate various suture materials and knot strengths in isolation of the tendon itself. This allowed us to evaluate mechanical differences between looped and non-looped sutures for polyamide, which are commonly used in flexor tendon repair. These differences between sutures may impact choices for a suture type selected for these repairs.